DDEL-15. METHOTREXATE AREA UNDER THE CURVE IN PRIMARY CNS LYMPHOMA. (14th November 2022) - Moussalli, Dana; Vo, Anh Huan; Turchan, Maria; Fu, Rochelle; Ambady, Prakash
Abstract: INTRODUCTION: There is consensus that high-dose methotrexate-based (HD-MTX) chemotherapy is the first line treatment for primary central nervous system lymphoma (PCNSL) but there is no consensus on drug dosing and duration. Area under the curve of Methotrexate (MTX-AUC) is a measure of exposure, and we hypothesize that a high MTX-AUC is associated with improved overall survival (OS) and progression free survival (PFS).Method: This retrospective study was approved by the institutional review board. HIV negative PCNSL patients who received Rituximab and HD-MTX at our institution from 2002-2020 were included. HD-MTX dose ranged from 1.2 gm/m 2 -8 gm/m 2 based on creatinine clearance. MTX-AUC was calculated using mtxpk.org. OS and PFS were analyzed using Kaplan-Meier method and Cox proportional hazard regression. Result: 34 PCNSL patient's charts (mean age: 67 yrs ± 15, 22F/12M) were reviewed. The mean MTX dose (5313 mg/m 2 ) strongly correlated with the mean MTX-AUC (3648 μmol*l −1 h, range: 698 – 6634). Patients with MTX-AUC < 3648 μmol*l −1 h median PFS is 44.6 months (95% CI: 3.8– non-estimable), not significantly different from patient with MTX-AUC > 3648μmol*l −1 h (PFS: 53.2 months, 95% CI: 4.3– non-estimable; P = 0.96). Results were similar after adjusting for patient characteristics in the Cox regression with hazard ratio (HR): 0.84; 95% CI: 0.29–2.43; P = 0.75). The median OS was 44.6 months (95% CI, 12.5– non-estimable) for patients with MTX AUC < 3648 μmol*l −1 h and not estimable for patients with MTX-AUC > 3648 μmol*l −1 h, HR of 0.43 (95% CI: 0.08–2.33; P = 0.33). Higher KPS prior to chemotherapy was associated with improved PFS/OS with HR: 0.95 (95% CI: 0.93–0.98; P = 0.0006) and HR: 0.91 (95% CI: 0.87–0.96; P = 0.0005) respectively. CONCLUSION: Our patients PFS and OS is improved compared to historical control but our data suggests that there is no statistically significant association with MTX-AUC in PCNSL.